A Methodological Approach Using rAAV Vectors Encoding Nanobody-Based Biologics to Evaluate ARTC2.2 and P2X7 In Vivo - Gondé, Henri; Demeules, Mélanie; Hardet, Romain; Scarpitta, Allan; Junge, Marten; Pinto-Espinoza, Carolina; Varin, Rémi; Koch-Nolte, Friedrich; Boyer, Olivier; Adriouch, Sahil (Frontiers in Immunology, 2021)
On murine T cells, mono-ADP ribosyltransferase ARTC2.2 catalyzes ADP-ribosylation of various surface proteins when nicotinamide adenine dinucleotide (NAD+) is released into the extracellular compartment. Covalent ADP-ribosylation of the P2X7 receptor by ARTC2.2 thereby represents an additional mechanism of activation, complementary to its triggering by extracellular ATP. P2X7 is a multifaceted receptor that may represents a potential target in inflammatory, and neurodegenerative diseases, as well as in cancer. We present herein an experimental approach using intramuscular injection of recombinant AAV vectors (rAAV) encoding nanobody-based biologics targeting ARTC2.2 or P2X7. We demonstrate the ability of these in vivo generated biologics to potently and durably block P2X7 or ARTC2.2 activities in vivo, or in contrast, to potentiate NAD+- or ATP-induced activation of P2X7. We additionally demonstrate the ability of rAAV-encoded functional heavy chain antibodies to elicit long-term depletion of T cells expressing high levels of ARTC2.2 or P2X7. Our approach of using rAAV to generate functional nanobody-based biologics in vivo appears promising to evaluate the role of ARTC2.2 and P2X7 in murine acute as well as chronic disease models.